#### To determine

**To find:** Make a rough sketch of the graph of function y=ln(-x).

#### Answer

see the graph

#### Explanation

**Step 1:** To draw the graph of y=ln(-x)**, ** we start with the graph of y=lnx. The

graph of y=lnx is (as given in Figure 3)

**Step 2:** Now we use the transformation g(x)=y(-x) to get the graph of y=ln(-x). We

invert the graph of y=lnx along y-axis to get the graph of y=ln(-x). Thus, the graph of the

function y=ln(-x) is

**Final statement:** see the graph

#### To determine

**To find:** Make a rough sketch of the graph of function y=ln|x|.

#### Answer

see the graph

#### Explanation

**Step 1-** To draw the graph of y=ln|x|**, ** we start with the graph of y=lnx. The

graph of y=lnx is (as given in Figure 3)

**Step 2:** Now we use the transformation g(x)=y|x| to get the graph of y=ln|x|. We take the

reflection of the graph y=lnx into y-axis and the reflection and original both would give the

graph of y=ln|x|. Therefor the graph of the function y=ln|x| is

**Final statement:** see the graph